2012
DOI: 10.5923/j.ajis.20120206.01
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Enhancement of Sports Images Using Two Comparative Approaches

Abstract: In this paper we have proposed two co mparative approaches for the contrast enhancement of dark sports images. The contrast of any image is a very important characteristic wh ich decides the quality of image. Lo w contrast images occur often due to poor or non uniform lighting conditions and sometimes due to the non linearity or small dynamic range of the imaging system. Enhancing the contrast of sports images is of importance since it is difficult to analyze the performance of the team or player with a poor q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The sigmoid is a nonlinear intensity enhancement function, which has been used in many imaging applications. The standard sigmoid function is described as follows (Kannan et al ., ): f(g)=11+eα(g) Where, g is the degraded image and α is a constant parameter that controls the enhancement of the function. In this study, an ameliorated version of the latter function is used to provide better intensity results, which is described as: f(g)=11+eα(gγ) Where, γ is an adjusting constant that by default, γ = 2.…”
Section: Proposed Tuned Brightness Controlled Single‐scale Retinexmentioning
confidence: 99%
“…The sigmoid is a nonlinear intensity enhancement function, which has been used in many imaging applications. The standard sigmoid function is described as follows (Kannan et al ., ): f(g)=11+eα(g) Where, g is the degraded image and α is a constant parameter that controls the enhancement of the function. In this study, an ameliorated version of the latter function is used to provide better intensity results, which is described as: f(g)=11+eα(gγ) Where, γ is an adjusting constant that by default, γ = 2.…”
Section: Proposed Tuned Brightness Controlled Single‐scale Retinexmentioning
confidence: 99%
“…Kannan P., Deepa S. and Ramakrishnan [2] presented two approaches for the enhancement of dark sports images. Low contrast images may occur because of poor lightning conditions or small dynamic range of imaging systems.…”
Section: Literature Surveymentioning
confidence: 99%
“…Figure 1 shows a schematic diagram of our proposed method for the segmentation of region of breast masses. The contrast of mass region in ultrasonographic image was first enhanced using a modified sigmoid function [21]. The region of breast mass was segmented by the novel level set method with the energy function consisted of three energy terms: a region-based term, edge-based term, and regularizing term.…”
Section: Methodsmentioning
confidence: 99%
“…c was a contrast factor, whereas th was the threshold value. In the modified sigmoid function, it is possible to change the amount of lightening and darkening to control the overall contrast enhancement by adjusting c and th [21]. Kannan et al reported that an optimal threshold value of th was between 0.3 and 0.5 [21].…”
Section: Contrast Enhancementmentioning
confidence: 99%